RELATIONSHIP BETWEEN HAND GRIP MUSCLE STRENGTH ON TOOTH BRUSHING RELATED TO DENTAL ABRASION - Frita Ferlita Shafri Djohan; Wahyuni Shofiani (Journal of Health and Dental Sciences, 2023)
Grip muscle strength in toothbrushing influences the brushing results. The strength has side effects, too, such as tooth abrasion. This study aims to systematically evaluate the results of tooth surface disappearance appraisal from toothbrushing in vitro and in vivo. Research methods performed by literature review with database articles search from Clinical Trials, Google Scholar, Cochrane Library, Pubmed, The International Clinical Trials Registry Platform (ICTRP), CINAHL with keywords. Articles were based on year, title, abstract, and full text and processed to final review. This research parameter utilized Optical profilometry from study designs: crossover and cross-sectional. Two full-text articles have been chosen, including inclusion criteria, and processed for final review. The study from Bizhang et al., abrasive toothpaste and toothbrush strength 2N, proves that manual toothbrushes have significantly less lead abrasion—manual toothbrush with wavy brush head 2.50(±0.43). Hara et al., reveal regimen B (erosion + toothbrushing with fluoride) day 28 (0,77±0,79) showed less loss of enamel surface than regimen C (erosion+toothbrushing without fluoride) day 28 (2,20±1,96). Prospecting the articles about the abrasion effect from toothbrush strength that are appropriate with the aim of study is still limited relating to abstract, full text, and keywords. The evaluation value of particular toothbrushing power will increase oral dental health without leading to severe abrasion risk on the dental surface. DOI : 10.54052/jhds.v3n2.p147-156